Hubungan Persepsi Pasien tentang Mutu Pelayanan Kesehatan dengan Minat Kunjungan Ulang Rawat Jalan di Puskesmas Bakunase Kecamatan Kota Raja - Aloysius S. S. Djuwa; Masrida Sinaga; Dominirsep O. Dodo (Universitas Nusa Cendana, 2020)
Public health center with good quality services will provide satisfaction and good perception to customers, which ultimately customers will reuse and recommend the health services to those around them. This will affect repeat purchasing decisions, which will affect consumers about the services provided. Bakunase Public Health Center data for 2016-2018 shows that Bakunase Public Health Center outpatient visits has decreased. The highest decline in outpatient visits to the Bakunase Public Health Center occurred in 2018, amounting to 15,354 visits. The purpose of the study was to analyze the relationship between patients perceptions about the quality of health services with the interest of outpatient visits at the Bakunase Public Health Center. This type of research is quantitative research with cross sectional research design. The population in this study was the average number of monthly outpatient visits at the Bakunase Public Health Center in 2018 of 3,468 people and a sample of 97 people taken using purposive sampling techniques. The results showed a relationship between perceptions of outpatients on the dimensions of reliability, assurance, empathy and direct evidence with the interest of outpatient visits in Bakunase Public Health Center. While the patient's perception of the responsiveness dimension is not related to the interest of outpatient visits at the Bakunase Public Health Center. It is expected that Bakunase Public Health Center can improve the quality of registration services, doctor services, shorten registration times and waiting times to get services.